The collaboration : Hollywood's pact with Hitler - Urwand, Ben, 1977- (The Belknap Press of Harvard University Press, 2013)
Explores "how Hollywood and especially the big studios went along with German demands to censor movies not only before but especially after the Nazi seizure of power"--Back of dust jacket